Peran dan Kewenangan Kejaksaan Agung dalam Penegakan Hukum Kasus Korupsi - Naila Zakiyatun Fakhiroh; Nina Desylia (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Corruption is a very serious form of crime that destroys the system of government, hinders development, and reduces public trust in state institutions. In terms of law enforcement in the country, the Attorney General's Office has an important position as an institution authorized to investigate and prosecute corruption cases. Based on Law Number 16 of 2004 together with Law Number 11 of 2021, the Attorney General's Office not only acts as a public prosecutor, but also as an investigator in corruption cases. This article aims to discuss the role and authority of the Attorney General's Office from a legal political perspective, as well as to analyze the various challenges faced in efforts to eradicate corruption. This research uses a normative juridical approach and legal politics, with a literature method through the study of laws and regulations, official documents, and scientific literature. The results of the study show that formally, the Attorney General's Office has a strong legal basis in handling corruption cases, including the authority to investigate, prosecute, and execute court decisions. However, in practice, the AGO faces various obstacles such as a weak legal system, a culture of impunity, political intervention, and limited human resources. To improve the effectiveness of law enforcement, it is necessary to strengthen institutional capacity, the independence of law enforcement officers, the utilisation of information technology, and synergy between law enforcement agencies. Anti-corruption education, public involvement in monitoring, budget transparency, and international cooperation are also important parts of the overall corruption eradication strategy. With a holistic approach, the Attorney General's Office is expected to be at the forefront of realising fair, transparent and accountable law enforcement.